The importance of papillary muscle dyssynchrony in predicting the severity of functional mitral regurgitation in patients with non-ischaemic dilated cardiomyopathy: a two-dimensional speckle-tracking echocardiography study - TİGEN, MUSTAFA KÜRŞAT (OXFORD UNIV PRESS, 2010)
In our study, we investigated the impact of papillary muscle systolic dyssynchrony (DYS-PAP) and the configuration of mitral leaflets in the prediction of significant functional mitral regurgitation (MR) with two-dimensional (2D) speckle-tracking strain analysis in non-ischaemic dilated cardiomyopathy (DCM) patients with sinus rhythm. Thirty-six non-ischaemic DCM patients (left ventricular ejection fraction < 40%) with sinus rhythm were recruited. The quantification of functional MR was performed using the proximal isovelocity surface area method. The configuration of mitral leaflets [mitral annulus, coaptation height (CH), and tethering distances for papillary muscles] was evaluated in the parasternal long-axis and apical four-chamber views. The assessment of DYS-PAP was performed by applying 2D speckle-tracking imaging to the apical four-chamber view for anterolateral papillary muscle and to the apical long-axis view for posteromedial papillary muscle. Fifteen (41.6%) patients had mild MR and 21 (58.3%) patients had moderate or moderate-to-severe MR. Patients with higher levels of MR had larger mitral annulus size (P = 0.02), tethering-AL (P = 0.04), higher MR volume (P < 0.0001), effective regurgitant orifice area (P < 0.0001), and DYS-PAP (P < 0.0001) values, but lower CH (P = 0.001), global longitudinal (P = 0.005), radial (P = 0.03), and circumferential strain (P = 0.01) than those with mild MR. Receiver operating characteristic analysis was performed to assess the utility of DYS-PAP to predict moderate or moderate-to-severe functional MR. A DYS-PAP value > 30 ms predicted moderate-to-severe MR with 85% sensitivity and 87% specificity [area under the curve: 0.897, 95% confidence interval (CI): 0.781-0.999, P < 0.0001]. Logistic regression analysis revealed that DYS-PAP (odds ratio: 3.2, 95% CI: 1.22-47.7, P = 0.037) was the only independent predictor of moderate or moderate-to-severe functional MR. DYS-PAP is correlated with functional MR in non-ischaemic DCM patients with sinus rhythm. A DYS-PAP cut-off value of 30 ms is a useful tool to identify patients with moderate-to-severe functional MR.
Keywords: Papillary muscle dyssynchrony; Mitral regurgitation; Dilated cardiomyopathy; CARDIAC-RESYNCHRONIZATION THERAPY; HEART-FAILURE; INTRAVENTRICULAR DYSSYNCHRONY; VENTRICULAR DYSSYNCHRONY; RADIAL STRAIN; MECHANISM